Multiple Renal Abscesses due to ESBL Extended-Spectrum Beta-Lactamase-Producing Escherichia coli Causing Acute Pyelonephritis and Bacteremia: A Case Report with a Good Outcome (No Drainage Required) - Abdalla Khalil; Musaad Qurash; Asem Saleh; Rasha Ali; Mohamed Elwakil (Case Reports in Infectious Diseases)
Extended-spectrum beta-lactamase-producing Enterobacteriaceae urinary tract infections are challenging infections with increased mortality, morbidity, and failure of therapy. A 44-year-old Saudi male diabetic patient was seen at the ER of IMC Hospital with features of acute pyelonephritis: fever, burning urine, and left flank pain for three days. He was treated for cystitis at the Endocrine Clinic two weeks prior to his ER visit with nitrofurantoin and levofloxacin orally according to urine culture and sensitivity result. The patient was admitted, received IV meropenem, and continued to be febrile for three days. His urine and blood culture at ER grew the same ESBL-producing E. coli as in his urine culture from the Endocrine Clinic. His abdomen CT scan showed two left renal abscesses at the upper and middle poles. His temperature resolved on the fourth day of IV therapy. Intravenous meropenem was continued for 4 weeks after inserting PICC line and the patient was followed up by home healthcare. He was feeling better with occasional left flank pain and repeated abdomen CT scan showed complete resolution of both renal abscesses.